KARAKTERISASI SABUN CAIR DENGAN VARIASI PENAMBAHAN EKSTRAK TEMBAKAU (Nicotiana tabacum L.) - Andi Eko Wiyono; Herlina Herlina; Nidya Shara Mahardika; Cahyan Ferdie Fernanda (JURNAL AGROTEKNOLOGI, 2020)
Liquid soap is a kind of cleanser made from a chemical reaction of the potassium salt of fatty acids. The distribution of soap with natural ingredients is rarely available on a market. One of the best options that can be used as a natural active ingredient of soap is a tobacco leaf. This study aimed was to the best treatment concentration of tobacco extract on the physical, chemical, and microbiological properties of liquid soap. The formulations of tobacco extract were 5%, 10%, and 15% of base soap. The study showed that the addition of tobacco extract to liquid soap could decrease the viscosity, specific gravity, pH, and alkaline free. Meanwhile, the nicotine level and bacterial inhibition (clear zone) were higher. The best concentration of liquid soap was formulation with the addition of 5% tobacco extract, with characteristics of viscosity about 2498.1 cP, specific gravity about 1.0209 g/mL, the stability of foam about 180 mL/ 9 hours, foam power about 22.34 second, pH 10.14, alkaline free about 0.0824%, nicotine content about 128.69 mg/100g and the antibacterial of E. coli (clear zone) of tobacco liquid soap about 5.8 mm. Keywords: liquid soap, natural active ingredients, tobacco extract